Dynamic control of volume phase transitions of poly(N‐isopropylacrylamide) based microgels in water using hydrazide‐aldehyde chemistry. Issue 12 (7th April 2014) - Chen, Yunhua; Ballard, Nicholas; Coleman, Oliver D.; Hands‐Portman, Ian J.; Bon, Stefan A. F.
ABSTRACT We demonstrate that the volume phase transition temperature (VPTT) of copolymer microgel particles made from N‐isopropylacrylamide (NIPAm) and methacryloyl hydrazide (MH) can be tailored in a reversible manner upon the reaction of the hydrazide functional groups with aldehydes. The microgels were synthesized by precipitation polymerization in water. Due to the water‐soluble nature of the MH monomer, the VPTT at which the microgel particles contract shifts to higher values by increasing the incorporated amounts of methacryloyl hydrazide from 0 to 5.0 mol %. The VPTT of the copolymer microgel dispersions in water can be fine‐tuned upon addition of hydrophobic/hydrophilic aldehydes, which react with the hydrazide moiety to produce the hydrazone analogue. This hydrazone formation is reversible, which allows for flexible, dynamic control of the thermo‐responsive behavior of the microgels. The ability to "switch" the VPTT was demonstrated by exposing hydrophilic streptomycin sulfate salt incubated microgel particles to an excess of a hydrophobic aldehyde, that is benzaldehyde. The temperature at which these microgels contracted in size upon heating was markedly lowered in these aldehyde exchange experiments. Transformation into benzaldehyde hydrazone derivatives led to assembly of the microgel particles into small colloidal clusters at elevated temperatures. This control of supracolloidal cluster formation was also demonstrated with polystyrene particles which had a hydrazide functionalised microgel shell. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1745–1754